Synergy of Islamic Communication in Building Environmental Love Character in Early Childhood - Feriana, Diah; Affandi, Akhmad; Suwendi, Ahmad (Edudeena : Journal of Islamic Religious Education, 2025)
Instilling environmental character in early childhood is an important foundation in forming a generation that cares about environmental sustainability. This article aims to examine how the synergy of Islamic communication between parents and teachers plays a strategic role in building environmental character in early childhood. This study uses a qualitative descriptive approach with a case study method. Data collection techniques use observation, interviews and documentation. Research data are analyzed using an interactive model. The results of the study indicate that Islamic communication patterns that are consistently applied by parents and teachers—based on values ​​such as compassion, role models, wise advice, and strengthening Qur'anic morals—are able to shape children's awareness of the importance of protecting and loving the environment. Harmonious collaboration between the family and school environments is key to creating an educational atmosphere that supports the formation of this character. The synergy of Islamic communication not only strengthens the relationship between adults and children, but also becomes an effective means of building children's ecological awareness from an early age. This approach is in line with Aristotle's eudaimonia thinking and Ibn Miskawaih's educational ethics. This study recommends strengthening communication collaboration between schools and families, integrating Islamic teachings into environmental education, and developing an ecological character education model based on spiritual values ​​as a real contribution to building environmental awareness from an early age.